PERLINDUNGAN HUKUM TERHADAP ANAK PELAKU TINDAK PIDANA PENGANIAYAAN - Lubis, Muhammad Ghalib Azmi (Law Jurnal, 2023)
Children are legal subjects and are responsible for compliance with the law. In the provisions of Law No. 23 of 2002, there are regulations to ensure efforts to protect children and their rights so that they can live, grow, develop, and participate optimally in a dignified manner and be protected from violence and discrimination. This research approach uses a statutory system combined with a case approach.In the results of the discussion, it was concluded that in the efforts to demand accountability carried out by teenagers for acts of violence as regulated in Article 170, paragraph 2, paragraph 1 of the Criminal Code, the complexity of the juvenile factor was finally included in the criminal act, and it was illustrated that the judge's consideration in handing down a sentence was based on the principle of legal certainty as the basis for handing down decisions, which focuses on Law Number 35 of 2014 concerning Amendments to the Child Protection Law Number 23 of 2002.